From Caliphate To Nation-State: Evolution Of Islamic Political Authority - Muhammad Alfi Syahrin; Khoiriyah; Heri Rifhan Halili; Babussalam (Al-Hikmah: International Journal of Islamic Studies, 2025)
This article examines the evolution of Islamic political authority from the caliphal ideal to the modern nation-state. The study argues that the transformation was not a simple decline from religious unity to secular fragmentation, but a layered shift in legitimacy, territory, law, citizenship, and institutional capacity. The caliphate historically functioned as a symbol of universal Muslim unity, yet practical authority was often mediated by dynastic rule, scholarly jurisprudence, imperial administration, and local political arrangements. The rise of colonial borders, constitutionalism, international law, and bureaucratic statehood reshaped Islamic authority into territorial forms governed by citizenship and public institutions. Using a qualitative conceptual-historical method, the article synthesizes recent scholarship on political authority, Islamic governance, state legitimacy, constitutionalism, and post-Ottoman political imagination. The findings show four patterns: the symbolic persistence of the caliphate, the territorial consolidation of the nation-state, the constitutional translation of Islamic norms, and the pluralization of religious-political authority. The discussion demonstrates that contemporary Islamic governance should not be reduced to restoring a single caliphal structure; rather, it requires ethical reconstruction within nation-state realities through justice, consultation, public welfare, accountability, and protection of citizenship. The article contributes a conceptual model for studying post-caliphal authority and offers implications for Islamic political thought, public policy, and future empirical research in Muslim-majority societies.